Adrenal Incidentaloma In Patient with Bilateral Nephrolithiasis and Infectef Right Kidney Cyst - kholidatul husna; Hermina Novida (Current Internal Medicine Research and Practice Surabaya Journal, 2020)
Adrenal incidentaloma (AI) is a rare case, with a prevalence of 3-7% in the general population. We report a case of a 66 year old female, presented with the history of bilateral flank pain. The patient was performed urologic evaluation due to suspicion of right perirenal abscess and left kidney tumor, and from abdominal CT scan it was found suprarenal mass. There were no signs and symptoms of hormonal hyperfunction. Radiological evaluation in the patient showed the present of malignant lesion. Therefore, adrenalectomy was planned. Before undergoing adrenalectomy, the patient had passed away 6 days after first surgery (right pyelolitotomy and unroofing cyst), with septic shock suspected as cause of death due to hospital-acquired pneumonia.